THE PERFORMANCE OF THE TEACHER AKIDAH AKHLAK IN DEVELOPING THE STUDENTS' CHARACTER AT MTs SWASTA BUSAK BUOL REGENCY - Nursanty, Ida; Syamsudduha, Sitti; Mardiana, Mardiana (Program Pascasarjana, UIN Alauddin Makassar, 2022)
The goal of this study was to provide an explanation for how moral akidah teachers at private MTs in Buol Regency were able to help pupils develop their character. The research method applied is qualitative research, the approach used is a psychological approach The informants of this research are the head of Madrasah, teacher of Akidah Akhlak, teacher of Al-Quran Hadith, and other general teachers. The data is collected through observation, interview, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. While testing the validity of the data is done by triangulation. The findings of this research indicated that although the Akidah Akhlak teachers at MTs Swasta Busak Buol Regency did an excellent job of developing their students' character, character development is still subpar and not at its best. The approach of habituation of everyday activities and spontaneous activities, example, and extracurricular activities used at MTs Swasta Busak Buol Regency to create student character Supporting elements at MTs Swasta Busak that help students develop their character include a dedication to the stringent enforcement of Madrasah laws and time management. Then, the limiting factor is made up of two elements: external ones, such teachers' lack of participation in activities, and internal ones, like the community's and the Madrasah's surroundings, particularly parents, who are not cooperating. The character development will have a major impact, if the Akidah akhlak teacher is prepared to develop students' character in a way that is appropriate for the subject matter. The second implication is that if the teacher of Akidah akhlak exercises management skills with regard to both classes and students as well as using various methods in accordance with the characteristics through character building, there will be an efficient process for fostering the character of students. The third implication will result in significant changes if madrasah leaders consistently carry out quality development activities for teachers, particularly Akidah Akhlak teachers, through coaching and training.